Microscopic haematuria at time of diagnosis is associated with lower disease stage in patients with newly diagnosed bladder cancer. (29th October 2015) - Ramirez, Daniel; Gupta, Amit; Canter, Daniel; Harrow, Brian; Dobbs, Ryan W.; Kucherov, Victor; Mueller, Edward; Streeper, Necole; Uhlman, Matthew A.; Svatek, Robert S.; Messing, Edward M.; Lotan, Yair
Abstract : Objectives: To determine whether the severity of haematuria (microscopic or gross) at diagnosis influences the disease stage at presentation in patients diagnosed with bladder cancer. Patients and Methods: We conducted a multi‐institutional observational cohort study of patients who were newly diagnosed with bladder cancer between August 1999 and May 2012. We reviewed the degree of haematuria, demographic information, clinical and social history, imaging, and pathology. The association of haematuria severity with incident tumour stage and grade was evaluated using logistic regression. Results: Patients diagnosed with bladder cancer presented with gross haematuria (GH; 1 083, 78.3%), microscopic haematuria (MH; 189, 13.7%) or without haematuria (112, 8.1%). High‐grade disease was found in 64% and 57.1% of patients presenting with GH and MH, respectively, and severity of haematuria was not associated with higher grade disease. Stage of disease at diagnosis for patients presenting with MH was Ta/carcinoma in situ (CIS) in 68.8%, T1 in 19.6%, and ≥T2 in 11.6%. Stage of disease at diagnosis for patients presenting with GH was Ta/CIS in 55.9%, T1 in 19.6%, and ≥T2 in 17.9%. On multivariate analyses, GH was independently associated with ≥T2 disease at diagnosis (odds ratio 1.69, 95% confidence interval 1.05–2.71, P = 0.03). Conclusions: Among patients with newly diagnosed bladder cancer, presentation with GH is associated with a more advanced pathological stage. Earlier detection of disease, before development of GH, could influence survival in patients with bladder cancer. Type of haematuria at presentation does not impact grade of disease.